(untitled) (MODERN CONSTRUCTION AND ARCHITECTURE, 2023)
The analysis of research works on the assessment of the stress-strain state of prefabricated metal corrugated structures of transport facilities was performed. It was established that the stresses and deformations of structures made of ZMGK depend on a complex of influencing factors: the amount of static and dynamic loads, the height of the backfill above the vault of the structure, the parameters of corrugation waves, etc. However, the interconnected effect of the pipe diameter and the thickness of the metal corrugated sheet on the stresses that occur in the metal pipe structures has not been established. The object of research is metal corrugated pipe constructions. To assess the stress state of the pipe, the influence on the stress of the cross-section of the pipe and the thickness of the metal corrugated sheet of the structure are taken into account. It was established that the geometric parameters of the cross-section of the pipe and the thickness of the metal corrugated sheet of the structure have a significant influence on the stress state of metal corrugated pipe structures. When the diameter of the pipe increases, the amount of stress that occurs in metal structures increases. However, with an increase in the thickness of the corrugated sheet, the amount of stress, with the same pipe diameter, decreases. Increasing the thickness of the sheet from 3.0 mm to 7.0 mm leads to a decrease in the stresses in the pipe metal by 50.39%. When the diameter of the pipe changes from 1.0 m to 6.0 m with a metal thickness of the corrugated sheet equal to 3.0 mm, the magnitude of the stresses increased by 7.38 times, with a sheet thickness of 4.0 mm ‒ by 7.8 times, with a thickness of 5.0 mm sheet – 8.08 times, 6.0 mm sheet thickness – 8.28 times, and 7.0 mm corrugated pipe sheet thickness – 8.43 times. It was established that the gradual increase in the thickness of the corrugated sheet of the structure leads to a decrease in the stress difference between the previous thickness of the sheet and the increased one. With a pipe diameter of 6.0 m, the stress difference that occurs when the thickness of the corrugated sheet is 3.0 mm and 4.0 mm is 21.35 MPa, with a thickness of 4.0 mm and 5.0 mm, the stress difference is 14.16 MPa, at 5.0 mm and 6.0 mm, the difference in stress values is 10.25 MPa, and with increased sheet thickness from 6.0 mm to 7.0 mm, the difference in stress values is 7.76 MPa. The obtained results of the stress state of prefab metal corrugated pipe structures can have practical application in the case of acceptance of the technical and economic justification, regarding the determination of the pipe diameter and the thickness of the metal corrugated sheet of the structure. One of the limitations of the application of these research results is the assessment of the stress state of the pipe made of prefabricated metal corrugated structures with the parameters of the corrugated waves of 150×50 mm. Other parameters of corrugation waves are not taken into account in this study.